O efeito de determinantes microeconômicos e conjunturais sobre a volatilidade dos retornos das principais ações negociadas no Brasil - Caselani, César Nazareno (2005)
This study aimed to explain the behavior of stock return volatility concerning the main stocks negotiated in São Paulo Stock Exchange (Bovespa) from January, 1995 through September, 2003. The study wanted to contribute in several ways for the understanding of stock return volatility in Brazilian market. First, it shows the theories and models developed to explain the determining factors of stock return volatility. Among those theories, this work explored leverage theory, volatility feedback theory, differences of opinion models and price– volume models. Another important contribution of this study was to use a sample of 35 stocks with minimum levels of liquidity using the study own methodology. Additionally, microeconomic and macroeconomic variables were added to the econometric models. Finally, this study discussed the results and their relation with the idiosyncrasies of Brazilian stock market. Among the results, it was observed that stock return volatility is influenced by the company leverage. In Brazil, stock return volatility follows the persistent behavior found in developed capital markets. The stock turnover tends to increase stock volatility. Maybe the high stock turnover is caused by new information increasing and revisions in stock prices. Those revisions stimulate stock return volatility. When the stock turnover occurs jointly with differences of opinion among investors, a higher turnover may produce stock return volatility. Contrary to the theory, the results didn’t corroborate the argument that stock return volatility is bigger when the return is negative. Additionally, results indicated influence of macroeconomic variables over the stock return volatility. A reduction in Brazilian GNP is associated with the increment in return volatility, possibly because it signalizes the perspective of recession. Also, stock return volatility increased in 1999 after the implementation of new exchange regime in Brazil. The study results showed that Brazilian stock market is not dependent of U.S. stock market. Finally, the inclusion of variables concerning the idiosyncrasies of Brazilian stock market showed interesting results. It seems that there is a positive association between stock return volatility and preferred stocks, maybe because Brazilian preferred stocks have higher turnover than common stocks and the lack of voting rights concerning preferred stocks increases the risk for investors. However, additional tests are necessary to confirm that association. Concerning the adoption of good corporate governance practices, the results of this study corroborate the argument that better corporate governance reduces stock risk.